2006
DOI: 10.1097/01.rli.0000188364.76251.28
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging at 3.0 Tesla Detects More Lesions in Acute Optic Neuritis Than at 1.5 Tesla

Abstract: The MRI protocol at 3.0 T was more sensitive to hyperintense brain lesions in ON than the standard MRI protocol at 1.5 T.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 31 publications
1
15
0
1
Order By: Relevance
“…There was no evidence that higher field strengths led to an earlier diagnosis of definite MS in patients with a clinically isolated syndrome [54] and no reliable data on whether there were more false positive diagnoses at 3 T as only 20 healthy volunteers were included [54]. There was no difference in inter-rater reliability between field strengths [53].…”
Section: Multiple Sclerosismentioning
confidence: 83%
See 2 more Smart Citations
“…There was no evidence that higher field strengths led to an earlier diagnosis of definite MS in patients with a clinically isolated syndrome [54] and no reliable data on whether there were more false positive diagnoses at 3 T as only 20 healthy volunteers were included [54]. There was no difference in inter-rater reliability between field strengths [53].…”
Section: Multiple Sclerosismentioning
confidence: 83%
“…Differences in numbers of enhancing lesions seen at 3 vs. 1.5 T were inconsistent, including 7.5 % [33] and 21 % [29] in two studies, but only 0.5/patient overall (P 0 NS) [53]. Few patients (2.8 % [32] to 3.6 % [53]) showed lesion enhancement only at 3 T. Suggested increases in lesion conspicuity on fluid attenuated inversion recovery (FLAIR) or T2-weighted imaging at 3 T ranged from 13 to 30 [34,36] (average difference 3.9 %) [53].…”
Section: Multiple Sclerosismentioning
confidence: 98%
See 1 more Smart Citation
“…First, the use of a 3T field strength likely played a role, in which there is theoretically a 3-fold increase in SNR from 1T that augments the visualization of abnormalities on SE-T2WI. [11][12][13][14] Second, SE-T2WI at 3T may display greater background white matter hyperintensity in premature patients, thus creating greater contrast of certain structures to background white matter. Third, the difference in rates of myelination detection between SE-T2WI and GRE-T1WI is slight and could even be accounted for by interobserver differences.…”
Section: Fig 4 Gre-t1wi (A and C ) And Se-t2wi (B Andmentioning
confidence: 99%
“…The first evidence that the new high field MRI generation provides higher lesion load measurements in MS patients was brought up by an intraindividual comparative study between 1.5 and 4 T. Keiper et al showed a 45% increase of T2 lesions using a 4-T compared to a 1.5-T scanner [25]. This higher sensitivity in the detection of focal MS lesions and/or lesion volumes could be conclusively confirmed by the subsequent studies comparing field strengths between 1.5 and 3 T including a total number 115 patients scanned with MRI scanners of three different vendors [26][27][28][29]. The increase in lesion numbers on T2/fluid-attenuated inversion recovery (FLAIR) images ranged from 13% to 41.6%.…”
Section: Conventional High Field Mri At 3 T In Multiple Sclerosismentioning
confidence: 89%